1993
DOI: 10.3102/0091732x019001171
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 5: The Organization of Effective Secondary Schools

Abstract: From its inception in the 1960s, the major focus of large-scale quantitative investigations of school effects has been on the issue of equal opportunities in education for disadvantaged and minority students. For two decades, school effects research attempted to identify the best way to deploy new federal resources for advancing educational equity. Beginning with the publication of the Equality of Educational Opportunity Report by James Coleman and others in 1966, this type of research was based on two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(8 citation statements)
references
References 204 publications
(265 reference statements)
1
7
0
Order By: Relevance
“…As theorized, schools with a sense of community will be resilient to crime-producing factors. Specifically, communal school organization is conceptualized as a community with members who know, care, and have common goals for the school (Lee, Bryk, & Smith, 1993;Payne, 2008Payne, , 2012Payne, Gottfredson, & Gottfredson, 2003). Schools that exhibit these communal characteristics have informal relationships and group participation to achieve goals.…”
Section: School Climatementioning
confidence: 99%
“…As theorized, schools with a sense of community will be resilient to crime-producing factors. Specifically, communal school organization is conceptualized as a community with members who know, care, and have common goals for the school (Lee, Bryk, & Smith, 1993;Payne, 2008Payne, , 2012Payne, Gottfredson, & Gottfredson, 2003). Schools that exhibit these communal characteristics have informal relationships and group participation to achieve goals.…”
Section: School Climatementioning
confidence: 99%
“…In small schools, the social network is more compact, which enhances (informal) interpersonal relationships, teacher collaboration, and close relationships between teachers and students. In such contexts, staff are more likely to engage in common activities and teachers have greater autonomy (Fowler and Walberg, 1991;Lee et al, 1993;Maslowski, 2001;Opdenakker and Van Damme, 2007). In larger school organisations, it is likely that more formal rules and procedures set the basis for activities; relationships may be more formal and staff members may have less autonomy (Lee et al, 1993;Maslowski, 2001).…”
Section: School Size and Proportion Of Beginning Teachersmentioning
confidence: 99%
“…In such contexts, staff are more likely to engage in common activities and teachers have greater autonomy (Fowler and Walberg, 1991;Lee et al, 1993;Maslowski, 2001;Opdenakker and Van Damme, 2007). In larger school organisations, it is likely that more formal rules and procedures set the basis for activities; relationships may be more formal and staff members may have less autonomy (Lee et al, 1993;Maslowski, 2001). This implies that school size could influence the way support is provided to and experienced by BTs.…”
Section: School Size and Proportion Of Beginning Teachersmentioning
confidence: 99%
“…Initial exploration showed that school averages of SES, political interest, and shares of immigrants were unrelated to our dependent variables, nor did they alter observed effects for other school-level predictors; they were excluded from further consideration. We do, however, control for school size as smaller school size has been linked with higher levels of student engagement (Lee, Bryk, & Smith, 1993; Lee & Smith, 1995). Moreover, we account for school type because semiprivate or private schools (especially Catholic schools) are more likely to foster civic skills (see Campbell, 2008a).…”
Section: The Present Studymentioning
confidence: 99%